Bioaugmentation, biostimulation and biocontrol - Singh, Ajay; Parmar,Nagina; Kuhad, Ramesh C. (Springer eBooks., 2011)
Bioaugmentation, biostimulation and biocontrol approaches using microbial inoculants, biofertilizers, biochemicals and organic amendments improve soil biology, fertility and crop productivity by providing plant growth-promoting nutrients and suppressing soil-borne diseases and plant-parasitic nematodes. Our knowledge of microbial diversity and its function in soils has been increased tremendously due to the availability of a wealth of data gained through recent advances in the development of molecular methods and metagenomics for the evaluation of microbial diversity and functions in the rhizosphere environment of soil. Chapters dealing with the application of biofertilizers and organic amendments are contributed by experts - authorities in the area of soil science including microbiology and molecular biology - from academic institutions and the industry.